Effect of self-representation of interaction history by the robot on perceptions of mind and positive relationship: a case study on a home-use robot. (2nd November 2019) - Mahzoon, Hamed; Ogawa, Kohei; Yoshikawa, Yuichiro; Tanaka, Michiko; Ogawa, Kento; Miyazaki, Ryouta; Ota, Yusaku; Ishiguro, Hiroshi
Abstract : A question in research is concerning the most important factors for increasing the motivation of a human to continue interacting with an interactional robot. Previous studies have argued that the perceptions of mind and interactability of the robot by the interacting human are essential factors. However, ways of improving such perceptions have not sufficiently investigated. In this study, we focused on the case of a home-use interactional robot and investigated ways to improve such perceptions. We proposed the perceived interaction history of the robot to be another essential factor and hypothesized that adding this factor can promote the perceptions of mind and positive relationship. We conducted a human–robot interaction experiment with 32 human subjects, and the experimental results verified our hypothesis. GRAPHICAL ABSTRACT: